Alkaloid Profile Characterisation and Bioactivity Evaluation of Bolivian Hippeastrum Species (Amaryllidaceae) as Cholinesterase Inhibitors - María Lenny Rodríguez-Escobar; Raúl Fernando Lara; Margoth Atahuachi; Alfredo F. Fuentes; Carla Maldonado; Jaume Bastida; Luciana R. Tallini; Laura Torras-Claveria (Life)
Amaryllidaceae alkaloids from the Amaryllidoideae subfamily exhibit broad pharmacological activities, including neuroprotection and anticancer effects. Galanthamine is a key compound for Alzheimer’s therapy. The Hippeastrum genus, particularly in Bolivia, offers significant potential for novel drug discovery, emphasising the need for conservation and further phytochemical research. Twenty-seven samples from Bolivian Hippeastrum species were investigated in terms of their alkaloid profile and anticholinesterase activity. The phytochemical analysis of Bolivian Hippeastrum species via GC-MS identified 48 Amaryllidaceae alkaloids, displaying diverse structural groups with potential pharmacological significance. Lycorine- and Homolycorine-type alkaloids were predominant, particularly in H. chionedyanthum and H. haywardii, with high concentrations of lycorine, a promising anticancer compound. The species H. evansiarum and H. mollevillquense contained notable quantities of Galanthamine type alkaloids, relevant for Alzheimer’s treatment. This study also highlights variability in acetylcholinesterase and butyrylcholinesterase inhibitory activities, with H. lara-ricoi and H. haywardii demonstrating strong inhibition. These findings suggest that Hippeastrum species are a valuable source of bioactive compounds, warranting further research into their therapeutic applications.